2004
DOI: 10.1149/1.1803837
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Metal Chlorides and Sulfates on the Formation of Beta-FeOOH Particles by Aerial Oxidation of FeCl[sub 2] Solutions

Abstract: To investigate the influences of metal ions on ␤-FeOOH formation, the ␤-FeOOH particles were prepared by aerial oxidation of FeCl 2 solutions in the presence of chlorides and sulfates of Ti͑IV͒, Fe͑III͒, Cu͑II͒, and Ni͑II͒, and CrCl 3 at different metal/Fe atomic ratios of 0-0.1 and characterized by X-ray diffraction, transmission electron microscopy, Fourier transform infrared spectroscopy, inductively coupled plasma, thermogravimetry and differential thermal analysis, and N 2 adsorption. The produced particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…It is well known that inorganic anions like chloride, carbonate, or sulfate have a strong influence on final product characteristics. 36 This same influence has been also observed at the chemical oxidation of Fe 2+ to obtain iron oxide films. 37 In the present work, the above mentioned ferrous sulfate bath has been used.…”
Section: Resultssupporting
confidence: 57%
“…It is well known that inorganic anions like chloride, carbonate, or sulfate have a strong influence on final product characteristics. 36 This same influence has been also observed at the chemical oxidation of Fe 2+ to obtain iron oxide films. 37 In the present work, the above mentioned ferrous sulfate bath has been used.…”
Section: Resultssupporting
confidence: 57%
“…The most characteristic SAED pattern observed in the crystals with this morphology is shown in Figure 11 image along this projection, showing structural ordering along all the crystal, is presented in Figure 11 It must be pointed out that when synthesized in the laboratory, akaganeite usually presents a spindlelike morphology. [34][35][82][83] In contrast, on the basis of the results obtained in this study, the typical morphology of akaganeite formed in atmospheric conditions seems to be of a rod-like type.…”
Section: Corrosion-july 2015contrasting
confidence: 61%
“…The pore structure of the rust layer is clearly related with steel corrosion because various molecules and ions such as O 2 , H 2 O, and Cl − diffuse through the rust layer in the corrosion process [ 146 , 163 ]. Despite this fact, few studies of rust pore structures have been reported.…”
Section: The Rust Layermentioning
confidence: 99%